Social entrepreneurship intention among public university students in Yemen - Humran, Mohammed Abbod Muthanna (2021)
The daunting challenges in Arab countries as a result of Arab Spring saddling polities and governments alike lead to failed governments and corporates to delivering public good and services to citizens. Whereby, resultantly created a large social gap represented by the slow growth of social development due to government failures. Moreover, countries with government’s failures in addressing social issues create a higher demand for attitudes and behaviors by individuals to create social value, which leads to increasing demand for social entrepreneurship. In ensuring and strengthening public-private partnership synergy to address social problems, with particular emphasis on leveraging acquired knowledge and skills of university students that could be harnessed to provide concrete and sustainable solutions for social challenges by utilizing social entrepreneurship as a key mechanism for dealing with social problems and adding economic and social value to sustainable social development. In view of this, this study aims to determine factors that have a significant relationship towards social entrepreneurship intention among public universities students in Yemen by using the theory of planned behavior (TPB). There were four independent variables included in this study, namely, attitude towards social entrepreneurship, subjective norms, perceived behavioral control, and prior experience. A total of 394 questionnaires were distributed among Hadhramout University students by using proportionate sampling. The results indicated that attitude towards social entrepreneurship, subjective norms, perceived behavioral control, and prior experience have a significant effect on social entrepreneurship intention among public universities students. The result has an implication to the existing body of knowledge; other researchers can explore the measurements in different sectors and contexts.